Rain forest recreation zone planning using geo spatial tools - Nordin, Roslina; Abdul Malek, Ismail Adnan; Mariapan, Manohar (Universiti Putra Malaysia Press, 2013)
Development and management of forest recreation areas require sound planning. Forest recreation planning is a process of planning recreation areas and their uses in a rational and systematic manner. It is based upon knowledge of the existing state of forest resources, identification of potential recreation sites, identifying pressures from surrounding physical development and the need for proper management of the sites. The advent of Global Positioning System (GPS) and Geographical Information System (GIS) technologies, with their efficient spatial data storage and analysis capabilities, has created a large field of opportunities for the development of new approaches to computer processing of spatial or geographically referenced data, hence, adding a new dimension to the management of large volumes of information needed in forest recreation planning. This paper describes the application of GPS and GIS technologies to map and identify forest recreation zones at Gunung Tebu Forest Reserve (GTFR), in Terengganu, Malaysia. Using GIS spatial modelling techniques, the location and extent of five recreation zones were identified: Campground (7.5 hectares), Hiking (13.7 hectares), Interpretive (4.4 hectares), Picnic (6.7 hectares), and Infrastructure (67.2 hectares). The study showed that GPS and GIS technologies are capable as Decision Support tools in forest recreation planning.